The Effect of Sharia Financial Literature, Government Support and Sharia Fintech on MSME Sustainability - Deni Pandu Nugraha; Iffan Ahmad Gufron; Pringgondani Pringgondani; Ilhamdi Ilhamdi (Institute of Computer Science (IOCS), 2022)
This study aims to formulate the importance of sharia financial literacy and sharia fintech to determine the sustainability of MSMEs which must be supported by appropriate government policies. This will determine the future strategy of MSMEs, in the sustainability of productivity and MSME development by accelerating the acceleration of sharia fintech adoption due to the pandemic-covid situation. In this causal research, data collection was done via online questionnaires to 236 SMEs between April 2021 and November 2021. Data analysis and path modeling was performed using smartPLS 3.0 software. The result shows that sharia fintech and government support have a direct influence on the sustainability of MSMEs. This indicates that an increase in the use of sharia fintech will increase the sustainability of MSMEs and government support can increase sustainability by making direct policies for MSME sustainability and indirect policies by increasing sharia fintech, meanwhile financial literacy sharia does not have a direct effect on the sustainability of MSMEs but has an indirect effect by increasing the use of sharia fintech.